2018
DOI: 10.3390/ijms19082289
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Heritable Pulmonary Arterial Hypertension Exert Convergent Actions on the miR-130/301-Vascular Matrix Feedback Loop

Abstract: Pulmonary arterial hypertension (PAH) is characterized by occlusion of lung arterioles, leading to marked increases in pulmonary vascular resistance. Although heritable forms of PAH are known to be driven by genetic mutations that share some commonality of function, the extent to which these effectors converge to regulate shared processes in this disease is unknown. We have causally connected extracellular matrix (ECM) remodeling and mechanotransduction to the miR-130/301 family in a feedback loop that drives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Levels of E2 and DHEA-S in PAH cases but not controls modulated the expression of miRNA-21, -29c, and -376a in circulating EVs and mirrored sex hormone-based associations with clinical markers. These miRNAs have been implicated in the pathobiology of PAH, vascular ischemic injury, and cancer (37)(38)(39)(40)(41)(42). This observation, along with the greater variability in miRNA expression over the cycle in PAH cases as compared to controls, suggests that E2 and DHEA-S stimulate hematopoietic signals and transcription of EV miRNA cargo to influence vascular and cardiopulmonary homeostasis in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of E2 and DHEA-S in PAH cases but not controls modulated the expression of miRNA-21, -29c, and -376a in circulating EVs and mirrored sex hormone-based associations with clinical markers. These miRNAs have been implicated in the pathobiology of PAH, vascular ischemic injury, and cancer (37)(38)(39)(40)(41)(42). This observation, along with the greater variability in miRNA expression over the cycle in PAH cases as compared to controls, suggests that E2 and DHEA-S stimulate hematopoietic signals and transcription of EV miRNA cargo to influence vascular and cardiopulmonary homeostasis in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study by Chen et al has demonstrated that increased expression of miR‐130b is associated with the downregulation of BMPR2 in experimental models of lung fibrosis (Chen et al, 2016). Overexpression of miR‐130a has been shown to reduce BMPR2 mRNA levels in human pulmonary vascular cells including endothelial cells and fibroblasts (Bertero et al, 2018). Consistent with these observations, we showed that miR‐130a/b downregulated BMPR2 expression by directly binding to its 3′UTR complimentary sequences in PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data offer evidence that the elevated expression levels of miR-130a may participate in the pathogenesis of different types of hypertension through pleiotropic effects on several target genes involved in vascular remodeling. 95 However, its therapeutic potential in hypertension remains to be addressed. Additionally, we observed that downregulated miR-126 and upregulated miR-145 are common for EHT and PAHT, while miR-204, miR-424, and miR-503 are downregulated in PAHT and PHT.…”
Section: Mirnas and Hypertensionmentioning
confidence: 99%